METAPHORS OF ANGER IN KARONESE LANGUAGE - Sri Ninta Tarigan, Mulyadi Mulyadi, Khairina Nasution, Darnadila Darnadila (Journal of International Crisis and Risk Communication Research, 2024)
The theory of Metaphor Concept is used in this research intwo steps. First, the research usedthe Image Scheme and the second was Cognitive Semantic. In this research, it was used to find types of anger metaphors that exist in the Karo language, observe how angry metaphors are conceptualized in the Karo language, and examine how to understand the concept of angry metaphors in the Karo language using cognitive semantics. This research used qualitative methods based on thetheory of Metaphor Concept. The data of this research were from angry people found in Karo Village, films, and books. All the data were divided using the Image Scheme, while cognitive semantics were used to give the background of the meaning of anger metaphors in the Karo language. The results of the research obtained 10 types of angry metaphor concepts that exist in the Karo language, and 20 types of angry metaphor concepts that are not found in Conceptual Metaphor Theory. The anger was the EDUCATION found in this study. Anger is EDUCATION, which still occupies the most conceptualized position in the Image Scheme and the meaning of the metaphorical concept of anger in Karo is obtained using cognitive semantics. The entire meaning of the angry metaphor concept in the Karo language is obtained from the background of the culture that emerged due to the influence of history, current developments, and social changes, of science in Karo society.